Border Crossings in and out of Europe - Ramos, M.; Pedro Figueiredo Neto; Daniele, G. (2022)
The aim of this publication is to offer readers a thorough overview of the variety of institutional and non-institutional European responses to the current influx of migrants from Africa, Asia and the Middle East. Tackling the complexity of such sensitive issues not only requires a multidisciplinary approach but also a set of contributions from different (inter)national perspectives, institutional or otherwise. The publication offers a critical debate on the subject of border(s) and culture crossings that non-European current immigration affords, seeking to address the way in which these are being absorbed into major ideological reconceptualisations of European national and extra-national identities (as well as forms of citizenship). It will focus on topics ranging from European history to regional demographics, from global economic trends to humanitarian issues, but will also discuss European integration and the recent rise of populist forms of nationalism, cultural interactions, ethnic-religious conflicts and securitisation of European external and internal borders. Founded on an interdisciplinary approach, the major goal of this publication is to provide an in-depth discussion on many of the key refugee issues that afflict the world today, as illustrated by the European case as hosting region. It will cover several themes including the question of borders and obstacles concerning the movement of people, refugees’ narratives and itineraries, international humanitarian law, hosting policies, refugee camps and other security (infra)structures.